2013
DOI: 10.3928/01484834-20130314-02
|View full text |Cite
|
Sign up to set email alerts
|

Empathy as a Determining Factor for Nursing Career Selection

Abstract: The ability to empathize with others is a highly desirable characteristic for the delivery of quality care by nurses. Little research is available that explores the empathy characteristics of students who are attracted to nursing. The purpose of this study is to explore whether empathizing and systemizing characteristics are important factors underlying students' self-selection into and continuing success in nursing programs and whether the importance of these characteristics tends to differ for men and women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 30 publications
0
19
2
2
Order By: Relevance
“…The authors have posed several reasons for this decline: a lack of appropriate role models; negative attitudes from academic staff; an intimidating educational environment; heavy classroom and clinical assignments; and patient negativity. Another area that may contribute to lower empathy levels is the systematization of nursing education,40 or in other words, developing a systems approach, being organised and integrating systems based thinking in their work, Penprase et al40 argued that systematization may be affected by increasing levels of critical thinking, increased theoretical knowledge, and the authors have also questioned the role that hospital systems play during the clinical placement education. Nursing education, in particular, has been criticized for not providing students with the necessary skills to empathize with their patients once in a clinical setting 13…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors have posed several reasons for this decline: a lack of appropriate role models; negative attitudes from academic staff; an intimidating educational environment; heavy classroom and clinical assignments; and patient negativity. Another area that may contribute to lower empathy levels is the systematization of nursing education,40 or in other words, developing a systems approach, being organised and integrating systems based thinking in their work, Penprase et al40 argued that systematization may be affected by increasing levels of critical thinking, increased theoretical knowledge, and the authors have also questioned the role that hospital systems play during the clinical placement education. Nursing education, in particular, has been criticized for not providing students with the necessary skills to empathize with their patients once in a clinical setting 13…”
Section: Discussionmentioning
confidence: 99%
“…Possible measures might include, but are not limited to, role playing, exposure to positive role models, and opportunities for improving narrative skills. These and other changes in nursing education are a way forward to enhance nursing students’ understanding of the patient’s perspective that will allow the students to engage with patients empathically and, ultimately, improve clinical outcomes 5,21,40…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[58][59][60] Preceptors also expressed concern regarding some students' motivation for becoming nurses. Their concern may be justified; however, there is current research that indicates students who select nursing as a career demonstrate substantially higher empathy scores compared to the general student population [61] and that experience as a nurse is not necessarily required for high levels of professional values. [62] The idea of preceptor as protector is not completely new.…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive study of 1,872 undergraduate students enrolled at a large Midwestern U.S. research-university identified that nursing students have a significantly higher degree of empathy for others as compared to students in a variety of other disciplines, including engineering. 9 This current study hinges upon the hypothesis that nursing theory provides a framework for engineers from multiple disciplines to improve the learning of 'practice'. A nurse is defined as, "a person who cares for the sick or infirmed who is skilled in promoting and maintaining health," (Merriam-Webster).…”
Section: Introductionmentioning
confidence: 99%